DEVELOPMENT OF COMPOSITE PROTECTIVE COATINGS FOR METAL SURFACES - Augustin Semenescu; Vili Pasare; Toma Fistos; Anda Maria Baroi (Nonconventional Technologies Review)
In order to increase the lifespan of epoxy coatings, the purpose of this work was to create a composite coating material, based on commercially available components, with high cohesion and a high degree of scratch resistance, which provides anti-corrosion protection for the metal support material, correlated with a method of pre-treatment of the support material.